Bilateral Spontaneous Hyphema in Juvenile Xanthogranuloma: A Case Report - Abdullah A. Al-Owaid (Case Reports in Ophthalmology, 2020)
Juvenile xanthogranuloma (JXG) is an idiopathic granulomatous inflammatory condition that usually affects children. Intraocular involvement, especially bilateral, is rare in JXG. Most patients with ocular lesions are typically infants and usually present with hyphema, iridocyclitis, and secondary glaucoma. We report a case of a 3-month-old baby girl who presented to our emergency department with bilateral hyphema that started 3 weeks ago. She was medically free with no history of any recent trauma or preceding febrile illness. General physical examination showed a quiet baby with multiple hyperpigmented macules over the inner thigh and right upper arm, with one pinkish nodule over the occiput. She also had high intraocular pressures. A detailed ophthalmic assessment was done under general anesthesia. The nodular lesion was excised and sent for histopathological evaluation, which confirmed the diagnosis of JXG. Treatment of JXG cases present a challenge to ophthalmologist due to rebleeding and refractory glaucoma. Our case was admitted multiple times for rebleeding and refractory glaucoma and was treated with full antiglaucoma drops, steroid drops and peribulbar injection of steroid.